The impact of breastfeeding on the health of HIV-positive mothers and their children in sub-Saharan Africa - Taha E Taha; Newton I Kumwenda; Donald R Hoover; George Kafulafula; Susan A Fiscus; Chiwawa Nkhoma; Shu Chen; Robin L Broadhead (Bulletin of the World Health Organization, 2006)
OBJECTIVE: We assessed the impact of breastfeeding by women infected with human immunodeficiency virus (HIV)-1 on their morbidity and risk of mortality and on the mortality of their children. METHODS: We analysed longitudinal data from two previous randomized clinical trials of mother-to-child transmission of HIV conducted between April 2000 and March 2003 in the Republic of Malawi, Africa. Mothers infected with HIV, and their newborns, were enrolled at the time of their child's birth; they then returned for follow-up visits when the child was aged 1 week, 6-8 weeks and then 3, 6, 9, 15, 18, 21 and 24 months. Patterns of breastfeeding (classified as exclusive, mixed or no breastfeeding), maternal morbidity and mortality, and mortality among their children were assessed at each visit. Descriptive and multivariate analyses were performed to determine the association between breastfeeding and maternal and infant outcomes. FINDINGS: A total of 2000 women infected with HIV were enrolled in the original studies. During the 2 years after birth, 44 (2.2%) mothers and 310 (15.5%) children died. (Multiple births were excluded.) The median duration of breastfeeding was 18 months (interquartile range (IQR) = 9.0-22.5), exclusive breastfeeding 2 months (IQR = 2-3) and mixed feeding 12 months (IQR = 6-18). Breastfeeding patterns were not significantly associated with maternal mortality or morbidity after adjusting for maternal viral load and other covariates. Breastfeeding was associated with reduced mortality among infants and children: the adjusted hazard ratio for overall breastfeeding was 0.44 (95% confidence interval (CI) = 0.28-0.70), for mixed feeding 0.45 (95% CI = 0.28-0.71) and for exclusive breastfeeding 0.40 (95% CI = 0.22-0.72). These protective effects were seen both in infants who were infected with HIV and those who were not. CONCLUSION: Breastfeeding by women infected with HIV was not associated with mortality or morbidity; it was associated with highly significant reductions in mortality among their children.